Indeks Pembangunan Ekonomi Inklusif Berwawasan Lingkungan di Indonesia - Wasudewa A.A. Ngurah Gede (P4W LPPM IPB, 2022)
Indonesian planners have been faced with significant challenges to change Indonesia‘s economic development paradigm. Economic development, which priorly focused on high development growth, were expected to become more inclusive and environmental friendly. The aim of this paradigm was to guarantee the sustainability aspect. To achieve this, standard criteria should be formulated during the planning stage, based on the level of environmental friendly inclusive economic development. Research should be conducted to provide these criteria and this research was aimed to formulate a composite index based on environmental friendly inclusive economic development concept. Method that are used to formulate these indexes are factors analyzing 21 variables that represent economic, social, and environmental variable. The result of this research is that the indexes of environmentally friendly inclusive economic development were composed of 5 factors, which is the level of economic infrastructure and growth, job opportunity, quality of the environment, basic infrastructure accessibility, poverty management and human resources capability. The calculation results of national and provincial Index of Environmental Friendly Inclusive Economic Development or IPEIBL value can be used as a reference in evaluating the achievement of inclusiveness and sustainable development in Indonesia by the government.